Lutas por reconhecimento em comunidades quilombolas da fronteira oeste do Rio Grande do Sul - Moreira, Cassiel Henrique (2022)
In Brazil, being part of a social minority is not a simple task, because, even though our country image is being a cordial, receptive and happy population, in reality, for its fellow countrymen, we are a violent and prejudiced country, that “kills”, depriving its population of basic rights, such as housing, food, education, employment and basic sanitation. These beings who do not have access to these rights usually have similar characteristics, they are black, poor, peripheral, the result of the construction of this nation, of a history that has not been repaired, we are talking about the black population that was enslaved, and that for years and years has been fighting to guarantee what is the basic right of the entire population. In this sense, to better understand how the process of the black quilombola population was in history, and what were the changes caused from this recognition, and if through this recognition there were impacts in relation to the access of public policies. Based on that, this dissertation sought, through the experiences of two Quilombola Communities on the West Frontier of Rio Grande do Sul, to analyze their trajectory and experiences through Axel Honnteh's theory of recognition, which considers recognition in three spheres, love, law and solidarity, involving primary relationships, the state and society, for this, a bibliographic research was also carried out on the theory and the theme, linked to a documentary research, with interviews with members of the communities, institutions partners, public authorities and other agents involved. In this way, the dissertation was divided into three chapters, the first addressing recognition in the sphere of love, analyzing the effects of primary relationships for self-recognition and the formation of an identity, in the second chapter it deals with public policies and law, presenting the trajectory from the creation to the access of public policies, such as land titling, health, rural extension and how access was made by these communities. The last chapter addresses the creation of quilombola associations and their effect within society, through recognition and their importance to their members and sectors of society, such as social movements and even public authorities. Therefore, through the study, it was possible to analyze the importance of ancestry for quilombola communities, for the formation of identity and maintenance of it, because knowing their history makes them who they are, another aspect evidenced was the fear of not having a continuity , because youth is one of the challenges. As for legal recognition, the impact of the recognition certificate issued by the Palmares Foundation on access to public policies was verified, an example of which is access to electricity and housing improvement. However, even so, some difficulties remain, the struggle remains constant, seeking through partnerships to maintain rights and create new opportunities, aiming at better living conditions for its population.